(3ENdGbjGJ GdEOGQI heSDhdjJg GdCYeGd aj TQcGJ GdCYeGds - (3YHhO fLe(B, (3fLes ((3YeGf(B:s (3eDSSI GdhQGb(B,s, 2006)
(3CNdGbjGJ GdEOGQI(B:(3GdeaGgje hGdJWhQ(B-(3bVGjG egeI aj CNdGbjGJ GdEOGQI(B-(3GdeSDhdjI GdELJeGYjI hCNdGbjGJ GdEOGQI(B-(3CNdGbjGJ GdEOGQI aj HYV GdJLGQH GdEOGQjI(B-(3GdeSDhdjI GdHjFjI hCNdGbjGJ GdEOGQI(B-(3CNdGbjGJ GdEOGQI hCNdGbjGJ GdegfIs
Keywords: (3EOGQI GdCYeGds; (3GdCNdGbs